Exploring the ethical awareness of using artificial intelligence in Algerian tertiary education: Case of undergraduate and graduate EFL students at Souk-Ahras University - Belouettar, Ayoub (Central European Journal of Educational Research, 2025)
Ethical awareness is a pivotal component of English as a Foreign Language (EFL) students’ identity in that it allows them to scrutinize their approach to learning which ensures their autonomy. Therefore, this study explores the ethical awareness of EFL students at Souk-Ahras University, Algeria. This study focuses on the use of Artificial Intelligence by students for their learning. It investigates their variating perceptions on and reactions towards AI for study and whether those views fit into the universal ethical code of conduct. This study employed a quantitative research approach with a descriptive research design. The sample studied consisted of 62 EFL students, selected through a random sampling technique. The collection of relevant data was done through a comprehensive survey. Data analysis was done using statistical analysis. The findings showed that students utilize AI tools for multiple learning purposes while being cognizant of its ethical drawbacks. However, students expressed a shallow approach to ethical reflection and did not rely on an authentic ethical framework upon which their decisions should be made. The study suggests that the development and employment of such a framework should start with teachers, by not merely disseminating charters but also delivering ethical scrutiny through their teaching and counselling.